Spindle cell variant of epithelioid cell histiocytoma (spindle cell histiocytoma) with ALK gene fusions: Cases series and review of the literature. (11th December 2020) - Kazlouskaya, Viktoryia; Ho, Jonhan; Jedrych, Jaroslaw; Karunamurthy, Arivarasan
Abstract: Background: Epithelioid fibrous histiocytoma (EFH) is an uncommon dermal neoplasm expressing anaplastic lymphoma kinase (ALK) protein. Rarely a histopathological variant of this entity exhibits exclusively spindle cells. We report three cases of EFH that do not completely fulfill phenotypic criteria featuring spindle cell morphology and expressing ALK protein. We also analyze the fusion partner genes rearranged with ALK in these cases. Methods: ALK expression and rearrangement status were evaluated by immunohistochemistry (IHC), fluorescence in situ hybridization (FISH), and next generation sequencing based gene fusion analysis. Results: Three cases, all from females between 25 and 55 years old, have been biopsied from back, left arm, and thumb. All three cases showed tumor with exclusively spindle cell morphology without any epithelioid cells. The tumor cells exhibited strong ALK expression by IHC and FISH study confirmed ALK gene rearrangement in all three cases. DCTN1‐ALK fusion was identified in two cases. Conclusion: EFH is not always purely epithelioid and its spindled cell variant, spindle cell histiocytoma, should be included in the differential diagnosis of superficial dermal spindled cell neoplasms. ALK immunostain is a useful diagnostic marker for this entity and further studies may be useful to investigate whether DCTN1‐ALK fusion mutations are specific to EFH with spindled cell features.